FINANCIAL PERFORMANCE EVALUATION OF INDONESIA STATEOWNED ENTERPRISES IN CONSTRUCTION INDUSTRY IN THE PERIOD OF 2014 â 3Q2020 (CASE STUDIES OF PT. WIJAYA KARYA TBK, PT. WASKITA KARYA TBK, PT. ADHI KARYA TBK, AND PT. PEMBANGUNAN PERUMAHAN TBK) - Nurfitriana, Annisa
Indonesia's most significant challenge today is to create an adequate infrastructure system along the islands to elevate livelihood and business competitiveness levels. The number of infrastructure construction projects has increased significantly from the beginning of Joko Widodo infrastructure agenda in 2014 until 2020. Each year, the government increases the infrastructure budget to create adequate infrastructure development to improve Indonesia's connectivity within the regions, intending to boost economic growth. Most infrastructure projects are given to state-owned enterprises in the construction industry. However, a sudden increase in projects today does not guarantee future workloads and performance. Therefore, companies' performance today is crucial. This research aims to assess four state-owned enterprises' financial performance and financial health conditions in the construction industry before the pandemic, from 2014 until 2019, and during the pandemic, third quarter of 2020. The four selected companies are PT Wijaya Karya Tbk (WIKA), PT Waskita Karya Tbk (WSKT), PT Adhi Karya Tbk (ADHI), and PT Pembangunan Perumahan Tbk (PTPP). The financial performance and financial health level assessment are based on the Decree of Ministry of Stated Owned Enterprises (SOEs) number iii